In-vitro Assessment of Inhibitory Capacity of Selected Woody Herbs on Isolated Fish Pathogens: In-vitro Assessment of Inhibitory Capacity of Selected Woody Herbs on Isolated Fish Pathogens - Abiola Fadilat Durojaiye; Silifat Adewunmi Olanloye; Musifat Abosede Kolapo (Journal of Aquaculture and Fish Health, 2026)
This study investigated the antimicrobial activity of Uvaria chamae, Nauclea latifolia, Anogeissus leiocarpus, Perquetina nigrescens, and Enantia chlorantha against the selected fish pathogens. Fish were divided into five treatments with concentrations of 0 mg/L, 50 mg/L, 100 mg/L, 150 mg/L, and 250 mg/L of the plant extracts. Minimum inhibitory concentration (MIC) tests were employed to determine the lowest effective concentrations of these extracts. Results showed that the aqueous extracts of these phytobiotics demonstrated significant antimicrobial potential. Generally, the control consistently showed higher MIC values across all pathogens, except P. nigrescens. Notably, U. chamae exhibited the lowest MIC values against Proteus vulgaris and Klebsiella species at concentrations of 50 mg/L and 100 mg/L, respectively. A. leiocarpus also showed effectiveness against Proteus vulgaris at 100 mg/L, while P. nigrescens had an MIC of 100 mg/L against the same pathogen. E. chlorantha was effective against Proteus vulgaris at 50 mg/L and Staphylococcus saprophyticus at 100 mg/L. Overall, P. nigrescens emerged as a compelling candidate for integration into aquaculture practices, with evidence of its ability to combat bacterial infections effectively while E. chlorantha displayed broad-spectrum antimicrobial activity, indicating its potential as a preventative measure. This study highlights the requirement for further research into the phytochemical constituents of these phytobiotics to better understand their mechanisms of action. Additionally, investigating synergistic effects when combined with other phytobiotics may enhance their overall antimicrobial profiles.